2017
DOI: 10.1177/0020872817712562
|View full text |Cite
|
Sign up to set email alerts
|

The likelihood of seeking help from social workers in Israel: Effect of gender, religiosity and prior experience of receiving professional help from social workers

Abstract: This study was conducted in Israel. It shows that women, religious people and those with prior experience of receiving professional help from social workers have a higher likelihood of seeking help from social workers than men, non-religious people and those who have never received professional help from social workers (respectively). The conclusion of the research is that social workers must be aware of population groups who have a lower likelihood of seeking their help, and must act to promote education amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 25 publications
3
11
0
Order By: Relevance
“…Studies indicate that past experiences of help-seeking (such as psychological help) have a significant effect on the likelihood of seeking such help in the future ( Gonzalez, Alegria, & Prihoda, 2005 ; Rickwood et al, 2005 ). It was identified that most of those who had prior experience with social workers remained satisfied with the services they received, and also had more knowledge and less uncertainty about the process of receiving social workers’ help, and accordingly reported a higher likelihood of seeking their help in the future ( Kagan & Zychlinski, 2017 ).…”
Section: Factors Related To Attitudes and Behaviors Associated With Smentioning
confidence: 99%
“…Studies indicate that past experiences of help-seeking (such as psychological help) have a significant effect on the likelihood of seeking such help in the future ( Gonzalez, Alegria, & Prihoda, 2005 ; Rickwood et al, 2005 ). It was identified that most of those who had prior experience with social workers remained satisfied with the services they received, and also had more knowledge and less uncertainty about the process of receiving social workers’ help, and accordingly reported a higher likelihood of seeking their help in the future ( Kagan & Zychlinski, 2017 ).…”
Section: Factors Related To Attitudes and Behaviors Associated With Smentioning
confidence: 99%
“…Studies on the association between gender and seeking both general and professional help, indicate that women are more willing to seek help and do so in practice more than men ( Andersson et al, 2013 ; Baum, 2006 ). Also, studies that relate specifically to SWs show that women have more positive attitudes towards them ( Kagan, 2016 ) and report a greater likelihood of seeking their help than do men ( Kagan & Zychlinski, 2016 , 2017 ). The studies ascribe this to women's higher ability to identify and recognize their predicaments and their need for help, higher readiness for emotional self-exposure, and greater social legitimization for seeking help ( Dahle, 2012 ; Mackenzie et al, 2006 ).…”
Section: Contribution Of Demographic Variables To Explaining the Like...mentioning
confidence: 99%
“…The studies portray an ambivalent picture of the association between age and seeking the help of helping and caring professionals in general and SWs in particular (i.e., Andersson et al, 2013 ; Kagan & Zychlinski, 2016 , 2017 ; Segal et al, 2005 ; Sirey et al, 2001 ). Some show a positive association between these variables since older people might contend with more issues that require professional help (for instance, with regard to physical or mental functioning) ( Kagan & Zychlinski, 2016 , 2017 ).…”
Section: Contribution Of Demographic Variables To Explaining the Like...mentioning
confidence: 99%
See 2 more Smart Citations